Expression, purification, and characterization of putative choline kinases from microorganisms - Khalifa., Moad Mahmoud Alarabi (2020)
Antimicrobial resistance (AMR) has been a menace to communities worldwide. AMR is estimated to cause ten million deaths a year by 2050. In bacteria, choline kinase (ChoK) is responsible for the synthesis of phosphorylcholine, which is a precursor for lipoteichoic acid and cell wall teichoic acid in Gram-positive bacteria. In Gram-negative bacteria, phosphorylcholine is incorporated into membrane lipopolysaccharides that modulate pathogen-host cell interactions. Choline kinase inhibitors (ChoKIs) that deteriorate the bacterial cell wall, have already been tested on Streptococcus pneumoniae with great results. ChoKIs activity can be also be enhanced by nanoparticles that act as a drug delivery system. The generation of the drug targets (bacterial ChoKs) in the form of recombinant proteins, is vital for testing the efficacy of ChoKIs. This study will attempt to address the issue of AMR by searching for the best conditions for the productions of recombinant ChoKs from Staphylococcus aureus (SaChoK), Neisseria meningitidis (NmChoK) and Haemophilus influezae (HiChoK) followed by in silico evaluation of these ChoKs as potential targets for ChoKIs by structural modeling and molecular docking approach. All three bacterial ChoKs were originally cloned in the pET14b vector for overexpression as His-tagged proteins. However, bioinformatic protein solubility prediction revealed that the solubility propensity of the His-tagged ChoKs tends to be less than the average soluble E. coli proteins. The protein overexpression in the periplasm using pGEX plasmid has been shown to increase protein solubility. Therefore, the SaChoK gene was subcloned from pET14b-SaChoK into a pGEX vector. Based on in silico prediction, the GST-tagged SaChoK, NmChoK, and HiChoK would be more soluble and produced at higher yields compared to His-tagged proteins produced from the pET14b vector. Molecular docking of SaChoK, NmChoK, and HiChoK model structures with Hemicholinium-3 (HC-3), an established small-molecule ChoKI, exhibited a fit binding mode inside the choline-binding pocket, indicating promising competitive inhibition by HC-3. Superimpositions of the three bacterial ChoK model structures with human ChoK revealed an ample homology, further supporting the use of ChoKIs previously used to inhibit human ChoK on AMR bacteria. The production of pGEX-SaChoK and the bioinformatic predictions have laid the groundwork for optimal overexpression of SaChoK, NmChoK, and HiChoK in E. coli system. The molecular docking results demonstrate the promising application of ChoKIs to combat AMR. Therefore, this study has paved the way towards successful overexpression of soluble recombinant bacterial ChoKs to be tested with currently available ChoKIs and reveal the potential of these compounds as antimicrobial agents.